Network slicing resource allocation algorithm based on bipartite graph matching in smart grids - Weiwei XIA; Yifei XIN; Dong LIANG; Jun WU; Xin WANG; Feng YAN; Lianfeng SHEN (Tongxin xuebao)
To solve the problem of simultaneously satisfying the quality of service requirements of multiple types of services in smart grids and considering the economic utility of power terminals and network side, a network slicing resource allocation algorithm based on bipartite graph matching was proposed.For the control and collection services in smart grids, the corresponding bidding information was formulated for the power terminals, and the payment price and utility matrix were calculated accordingly.The resource allocation between the network slices and the power terminals was modeled as a bipartite graph matching problem.Different slicing resources were allocated to the terminals according to the latency, transmission rate, or energy consumption requirements of different services to maximize the system utility.Simulation results show that the proposed algorithm is able to improve the system utility by 10%～20% compared to the existing double auction algorithm and greedy algorithm.